Enhanced stability of vitamin A palmitate microencapsulated by γ-cyclodextrin metal-organic frameworks. (3rd April 2018) - Zhang, Guoqing; Meng, Fanyue; Guo, Zhen; Guo, Tao; Peng, Hui; Xiao, Jian; Liu, Botao; Singh, Vikaramjeet; Gui, Shuangying; York, Peter; Qian, Wei; Wu, Li; et al.
Abstract: γ-Cyclodextrin metal-organic frameworks (γ-CD-MOFs) are highly porous and bio-friendly novel materials formed by γ-CD as an organic ligand and potassium ion as an inorganic metal centre. The aim of this study was to enhance the stability of vitamin A palmitate (VAP) using γ-CD-MOFs as the carrier. Herein, γ-CD-MOFs displayed VAP microencapsulating capacity of 9.77 ± 0.24% with molar ratio as n MOFs : n VAP = 3.2:1.0. It was important to find that the improved stability of VAP microencapsulated by γ-CD-MOFs without addition of any antioxidant(s) was better than that of the best available reference product in the market, with 1.6-fold elongated half-life. The protecting mechanism of γ-CD-MOFs for VAP contributed that VAP molecules preferentially curled inside the cavities of dual γ-CD pairs in γ-CD-MOFs. It was proved that γ-CD-MOFs were an efficient new carrier to deliver and protect VAP for food and pharmaceutical applications.